In vivo self-assembly and delivery of VEGFR2 siRNA-encapsulated small extracellular vesicles for lung metastatic osteosarcoma therapy - Lingfeng Yu; Gentao Fan; Qingyan Wang; Yan Zhu; Hao Zhu; Jiang Chang; Zhen Wang; Shoubin Zhan; Xianming Hua; Diankun She; Jianhao Huang; Yicun Wang; et al. (Cell Death and Disease, 2023)
Abstract The prognosis of lung metastatic osteosarcoma (OS) remains disappointing. siRNA-based gene silencing of VEGFR2 is a promising treatment strategy for lung metastatic OS, but there is a lack of safe and efficient delivery systems to encapsulate siRNAs for in vivo administration. This study presented a synthetic biological strategy that remolds the host liver with synthesized genetic circuits for efficient in vivo VEGFR2 siRNA delivery. After being taken-up by hepatocytes, the genetic circuit (in the form of a DNA plasmid) reprogrammed the liver to drive the autonomous intrahepatic assembly and encapsulation of VEGFR2 siRNAs into secretory small extracellular vesicles (sEVs), thus allowing for the transport of self-assembled VEGFR2 siRNAs towards the lung. The results showed that our strategy was superior to the positive medicine (Apatinib) for OS lung metastasis in terms of therapeutic efficacy and toxic adverse effects and may provide a feasible and viable therapeutic solution for lung metastatic OS.